Wear - Scott, D. (Douglas), 1916- (Treatise on materials science and technology, 1979)
Treatise on Materials Science and Technology, Volume 13: Wear provides a state of the art review of wear to form a basis for all future work on the subject and to be a standard work for all in the field. The book discusses the theories of wear and their significance for engineering practice; the wear of polymers; and the wear of carbons and graphites. The text also describes scuffing with regard to its physical manifestations, its importance in practice, theoretical interpretations advanced to describe and explain its occurrence. Abrasive wear; fretting; erosion caused by impact of solid parti.